The Duchet conjecture - Prakash, V.; Parthasarathy, K. R.; Rangan, C. Pandu (Indian National Science Academy, 1998)
In this paper, we investigate a conjecture of Duchet that r(G)≤η(G)+1, where r(G) is the Radon number and η(G) is the Hadwiger number of a graph G. In this paper, we give a class of counter examples for which rg(G)=η(G)+2, where rg(G) is the Radon number for the g-convexity structure. On the positive side, we prove the conjecture for some special classes of graphs like cycles and chordal graphs.